Negotiated transfer prices - Johannes Becker; Ronald B. Davies (University College Dublin, UCD School of Economics, 2015)
The predominant model of tax induced transfer pricing is based on the assumption that profit shifting is due to insufficient enforcement. However, evidence shows that the firms responsible for most profit shifting are also among the most frequently audited. We present an alternative model based on negotiations that avoid costly, yet uncertain, formal proceedings (e.g. court procedures). This model predicts that profit shifting increases in the tax gap even though enforcement is perfect. Further, it suggests that current efforts to streamline international tax law may have the unintended effect of increasing profit shifting.
Keywords: H25; H32; H87; 330; transfer pricing; Nash bargaining; tax avoidance; corporate taxation